1982
DOI: 10.1055/s-0038-1657212
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Platelet Release in Myeloproliferative Disorders

Abstract: SummaryThe in vivo platelet release reaction in 22 patients with myeloproliferative disorders has been studied by measuring plasma concentrations of the platelet release product β-throm-boglobulin (βTG). Mean βTG and mean βTG:whole blood platelet count ratio were significantly raised in the patient group taken as a whole compared to an age matched control group. No significant increases were observed in the plasma concentrations of thrombin and plasmin sensitive fibrinogen fragments fibrinopeptide A (FpA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
18
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 7 publications
5
18
0
Order By: Relevance
“…The facts that increased plasma levels of a-granule proteins were found in all patients and that PF4 plasma levels were correlated with the platelet count suggest that increased levels of a-granule proteins in MPD patients do not necessarily indicate platelet activation in the circula tion, but rather, the inability of MPD plate lets to store these proteins properly. The lack of significantly elevated FPA levels is in agreement with this hypothesis and corrobo rates results obtained by Ireland et al [ 1982] who found normal or slightly increased lev els of the fibrinogen fragments FPA and B(i 1-42 despite increased a-granule release. However, platelet function disorders in MPD patients may be related to abnormali ties of platelet morphology as there was con siderable variation of platelet volume heter ogeneity between patient subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…The facts that increased plasma levels of a-granule proteins were found in all patients and that PF4 plasma levels were correlated with the platelet count suggest that increased levels of a-granule proteins in MPD patients do not necessarily indicate platelet activation in the circula tion, but rather, the inability of MPD plate lets to store these proteins properly. The lack of significantly elevated FPA levels is in agreement with this hypothesis and corrobo rates results obtained by Ireland et al [ 1982] who found normal or slightly increased lev els of the fibrinogen fragments FPA and B(i 1-42 despite increased a-granule release. However, platelet function disorders in MPD patients may be related to abnormali ties of platelet morphology as there was con siderable variation of platelet volume heter ogeneity between patient subgroups.…”
Section: Discussionsupporting
confidence: 91%
“…These observations are compatible with those of Ireland [16] who has shown an increase of ␤TG and PF4 in the overall group of ET patients. Thus, these disturbances cannot be linked with the variability of clinical complications among ET patients.…”
Section: Discussionsupporting
confidence: 93%
“…The amount of serotonin stored in platelet-dense bodies is, in fact, statistically reduced in patients with MPD [5,9], whereas normal content of alpha granules has been reported [15]. Other studies demonstrate, in patients with MPD, high amounts of circulating ¡kg [7,13,16] and low content in alpha granules [4] as a consequence of the platelet activa tion in vivo. Our findings confirm the re duced content of serotonin in patients with MPD, but the results of the measure ment of (kg require further explanations.…”
Section: Discussionmentioning
confidence: 99%